Contracting State as key role in Public Management (2016)
By this test, an analysis of the importance of State Procurement in Public Management, presenting classes existing contracts in Colombia, the different types of contracts, and the principles set forth in the General Contracting. Similarly, it is intended to explain the importance of the contractual process generated between state agencies and the private sector, in order to meet the needs of the population, wherein said process depends mostly in an efficient budget execution through the implementation of budget Availability Certificate in entities that are part of the General budget of the Nation.